Employing industrial cluster concept as a strategy to improve small industries in Kelantan, Malaysia - Yohan Kurniawan; Wan Mohamad Wan Abdullah; Hishamuddin Md.Som; Balakrishnan Parasuraman (2013)
Asean became a major focus for international capitalism, with a population of over 300 millions and reported to be some of the higher per capita incomes in the Third World with market potential; This may be due the possibilities for investment given its low labour costs and comparative political stability, its strategic position between the Indian and Pacific oceans and the 'openness' of the economies to trade, foreign investment and the activities of multinational corporations. However, the welfare of the community in Southeast Asia is still not resolved and the poverty rate is still relatively high. One way is to construct industrial clusters comprising of small and medium enterprises in the village. An industrial cluster is different from the classic definition of industry sectors because it represents the entire value chain of a broadly defined industry from suppliers to end products, including supporting services and specialized infrastructure. Cluster industries are geographically concentrated and inter-connected by the flow of goods and services, which is stronger than the flow linking them to the rest of the economy. Clusters include both high and low-value added employment. The purpose of this paper is to examine the industrial clusters namely in the Tumpat rural community, Kelantan, Malaysia. The Industries involved in this project are the traditional cake and industrial catfish industries. There were 17 respondents in this programme working closely with rural industry. The concept of industrial clusters identified in this project is related with developing primary industries, which are aimed to advance the economy in the community. The industrial clusters constrcuted for catfish industry are pellet industry, catfish crackers industry, catfish breeder, etc. and the traditional cake industry constructed are the pineapple jam industry, printing industry, peanut farming, cake industry hub, etc. If the main business and their industrial clusters grow, there will be increased in the community welfare. The limitations faced by these industrial clusters are financial problem (lack capital business), entrepreneur motivation, lack of interest among the rural community, and also lack of strategic management, marketing, and finance management knowledge in addition to lack of networking